Some Statistical Properties of Linear Volterra Integral Equation solutions - Hussein, A.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Our aim of this research is to find the results of numerical solution of Volterra linear integral equation of the second kind using numerical methods such that Trapezoidal and Simpson's rule. That is to derive some statistical properties expected value, the variance and the correlation coefficient between the numerical and exact solutionâ–¡